Left Ventricular Assist Devices (LVADS): History, Clinical Application and Complications - Eisen, Howard J. (Korean Circ J, 2019)
Congestive heart failure is a major cause of morbidity and mortality as well as a major health care cost in the developed world. Despite the introduction of highly effective heart failure medical therapies and simple devices such as cardiac resynchronization therapy that reduce mortality, improve cardiac function and quality of life, there remains a large number of patients who do not respond to these therapies or whose heart failure progresses despite optimal therapy. For these patients, cardiac transplantation is an option but is limited by donor availability as well as co-morbidities which may limit survival post-transplant. For these patients, left ventricular assist devices (LVADs) offer an alternative that can improve survival as well as exercise tolerance and quality of life. These devices have continued to improve as technology has improved with substantially improved durability of the devices and fewer post-implant complications. Pump thrombosis, stroke, gastrointestinal bleeding and arrhythmias post-implant have become less common with the newest devices, making destination therapy where ventricular assist device are implanted permanently in patients with advanced heart failure, a reality and an appropriate option for many patients. This may offer an opportunity for long term survival in many patients. As the first of the totally implantable devices are introduced and go to clinical trials, LVADs may be introduced that may truly be alternatives to cardiac transplantation in selected patients. Post-implant right ventricular failure remains a significant complication and better ways to identify patients at risk as well as to manage this complication must be developed.